Sequelae and mortality in patients with HIV/AIDS and Progressive Multifocal Leukoencephalopathy: Systematic review and case series in the Brazilian Amazon - Valente, Jefferson; Del-Tejo, Paola López; Cubas-Vega, Nadia Carolina; Rodrigues, Maria Gabriela de Almeida; de Barros, Francisco Railson Bispo; Alexandre, Márcia Araújo; Arêas, Guilherme Peixoto Tinoco; Bastos, Michele; Pinto, Sérgio Damasceno; Barros, Camila Miriam S. S.; Marinho, Eveny Perlize; Mello, Sabrina; et al. (Frontiers in Tropical Diseases, 2023)
Background Progressive Multifocal Leukoencephalopathy (PML) is an opportunistic neurological disease that mainly affects individuals with HIV/AIDS and has high morbidity and mortality, due to its demyelinating characteristic. This co-infection has been reported since the begging of HIV/Aids epidemic with increasing unfavorable outcomes, however, factors associated to sequelae and death are greatly unknown. In this study we aimed to understand factors associated with the main outcomes of individuals diagnosed with PML and HIV/AIDS, in addition to reporting the characteristics of patients presenting to a referral center in infectious diseases in the Brazilian Amazon. Methods A systematic review was performed until July 2022, following the PRISMA guidelines, at Medline/Pubmed, Web of Science, Lilacs and Scielo databases using combinations of HIV, Aids, JC Virus and Progressive Multifocal Leukoencephalopathy, with no restriction to publication date. Additional cases, meeting the eligibility criteria, were added from our hospital database, which consisted of patients presenting PML/HIV between 2010 and 2022. A meta-analysis aiming to explore factors associated to sequelae and death was performed. Baseline characteristics were described using mean and standard deviation, or median and interquartile range when appropriate; multivariate analysis was performed to study factors associated to death and sequelae outcomes. Results Eighteen patients were diagnosed between 2010 and 2022, of these, 10 had positive PCR for JC virus. In the Systematic Review, 216 studies yielded 235 confirmed cases of co-infection. A total of 245 were included for analysis. The rates of death and sequelae were, respectively, 47.1% (114/242) and 41.2% (54/131). The use of antiretroviral therapy was more associated with a lower chance of death (OR 0.30, 95% CI: 0.11-0.83), while muscle weakness (OR 4.82, 95% CI: 2.07-11.21) and muscle spasms (OR 6.12, 95% CI: 1.05-35.76) were associated with greater chances of sequelae. Conclusion Those on antiretroviral therapy appear to be less likely to die, and among those who survive, those who have muscle weakness as a symptom on admission are more likely to develop sequelae. Adherence to ART, as well as a comprehensive clinical evaluation and follow-up may help to improve clinical outcomes and awareness of morbidities.